The microstructural characteristics in a newly developed nickel-base cast superalloy - Yao, XX; Fang, Y; Kim, HT; Choi, J (ELSEVIER SCIENCE INC, 1997)
A new cast superalloy with composition of 8.48 Cr, 9.68 W, 1.76 Mo, 4.52 Al, 0.95 Ti, 9.55 Co, 1.02 Nb, 5.16 Ta, 0.07 Hf, 0.082 Zr, 0.013 B, 0.11 C, Ni bal. (wt.%) was prepared by the investment casting process. The alloy was solution annealed at 1553K for 2h and then air cooled, followed by a two-step aging treatment for 5h at 1293K and then air cooled, followed by 1143K and air cooled to room temperature. The microstructural characteristics were evaluated through optical and electron microscopic observations. Electro probe microanalysis and energy-dispersive analysis of X-rays were conducted to study the (W, Mo)-rich phase precipitated in the new alloy. The results showed that the alloy is coarse grained (similar to 5mm) with serrated grain boundaries and a relatively homogeneous composition. This alloy contains uniform gamma-gamma' microstructure and a fine, discrete W-Mo-containing phase together with discrete carbides M6C and M23C6, which coexist at grain boundaries. All of these microstructural features are thought to be beneficial to the superior creep rupture life of the newly developed nickel-base superalloy. (C) Elsevier Science Inc., 1997.
Keywords: ALLOYS; GROWTH